2020
DOI: 10.1007/978-3-030-42970-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Applying Dynamic Performance Management to Public Emergency Management: An Analysis of the Wenchuan Earthquake

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Whilst the literature on performance is already combined with simulation (Bianchi, 2016), with a few exceptions (Wang et al, 2020a(Wang et al, , 2020b, the resulting frameworks have not been applied to DM studies. However, in the analysed articles, simulation is mainly examined from the performance point of view.…”
Section: Medarmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the literature on performance is already combined with simulation (Bianchi, 2016), with a few exceptions (Wang et al, 2020a(Wang et al, , 2020b, the resulting frameworks have not been applied to DM studies. However, in the analysed articles, simulation is mainly examined from the performance point of view.…”
Section: Medarmentioning
confidence: 99%
“…Indeed, the implementation of digital technologies are becoming increasingly relevant for corporate and performance management (Oliver, 2018;Marrone and Hazelton, 2019;Wang et al, 2020aWang et al, , 2020bChatterjee et al, 2021;Jun et al, 2021), and especially ETs have demonstrated in the last years to be particularly supportive in fostering these issues in health care (Spanò and Ginesti, 2021), transportation (Chhabra et al, 2021), manufacturing (Rezaei et al, 2017) and so on.…”
Section: Introductionmentioning
confidence: 99%